Women leaders and the church 3 crucial questions - Belleville, Linda L. (Grand Rapids, MI Baker, 2000)
Includes bibliographical references and indexes.
Keywords: Women clergy -- biblical teaching; Women -- biblical teaching; Leadership -- biblical teaching; Women in Christianity -- history -- early church, ca. 30-600.